Method for evaluating dewatering performance of pre-oxidation conditioning sludge
By measuring the electron acceptance and supply capacity of sludge dissolved organic matter, the dewatering performance of pre-oxidation conditioning sludge is quickly and accurately evaluated, and the problems of diversified types of oxidation agents and difficulty in controlling the dosage in the existing technology are solved, and accurate evaluation and optimization control of the dewatering performance of sludge are achieved.
Patent Information
- Application Number
- CN202510063825.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-05-02
AI Technical Summary
The existing sludge preoxidation technology has the problem of a variety of oxidation agents and difficulty in controlling the dosage of oxidation agents, which makes it difficult to accurately control the oxidation degree and affects the sludge dehydration efficiency.
By measuring the electron acceptance and supply capacity of sludge dissolved organic matter, the relationship between these sludge and sludge dehydration performance indicators is quickly and accurately evaluated.
This method can be applied to sludge of different initial pH and temperature, avoiding the problem of poor sludge dewatering performance caused by weak oxidation and strong oxidation caused by the inability to accurately evaluate the sludge dewatering performance in pre-oxidation conditioning, and achieving a rapid and accurate evaluation of sludge dewatering performance.
Smart Images

Figure CN119915787A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sludge treatment, in particular to a method for evaluating the dewatering performance of pre-oxidation conditioned sludge. Background Art
[0002] A large amount of sludge is inevitably produced during the sewage treatment process. These sludges have the characteristics of high water content, large output, and high difficulty in treatment, which brings huge challenges to the sewage treatment field. As of 2020, my country's annual sewage treatment capacity reached 89.5 billion tons, and the sludge output exceeded 47 million tons. The residual activated sludge produced in the sewage treatment process usually contains 95-99% water, and its treatment and disposal cost accounts for about 35-65% of the operating cost of the sewage treatment plant. Therefore, it is urgent to develop technologies to reduce the sludge moisture content, minimize the sludge volume, facilitate transportation and improve energy efficiency. However, a large amount of water is combined with sludge flocs and microbial cells, causing the sludge to be highly hydrophilic, which limits the dewatering efficiency of the sludge. Sludge usually contains 70% free water and 30% bound water. The free water can be removed by mechanical dewatering methods such as plate and frame filter press and belt filter press. The removal of bound water is usually difficult to remove by conventional flocculants, and its removal efficiency is a key factor affecting the sludge dewatering efficiency. At present, the addition of traditional chemical conditioners (such as coagulants such as ferric chloride and polyacrylamide) can aggregate the sludge to form larger flocs through charge neutralization and adsorption bridging, and then mechanical dehydration can only reduce the moisture content of the mud cake to about 80%, which cannot meet the sludge treatment and disposal standards in my country. Therefore, in order to improve the dehydration performance of sludge and achieve deep dehydration, pre-oxidation technology is often used to effectively destroy, dissolve and reduce extracellular polymers (EPS), convert bound water into free water, and improve the dehydration performance of sludge. For example, Chinese patent CN201310491976.9 mentions that iron salts prepared by using a mixture of ferrous sulfate, calcium oxide and magnesium oxide can shorten the sludge dehydration time and reduce the cost of sludge dehydration. Among them, calcium oxide and magnesium oxide play a pre-oxidation role under the activation of divalent iron, releasing bound water. For example, Chinese patent CN201110300223.6 proposes a sludge dehydration composite conditioning agent composed of Fenton reagent or / and Fenton-like reagent and a skeleton construct and its application method. Among them, Fenton or Fenton-like reagent plays a role of pre-oxidation, which can effectively destroy extracellular polymers in sludge and reduce the compressibility of organic matter. However, the use of existing pre-oxidation technology has the disadvantages of various types of oxidants and difficult control of the dosage of oxidants. The oxidation efficiency of pre-oxidation and the effect on sludge dehydration depend on various factors, including the type, dosage, oxidation time, pH value, sludge type, sludge concentration and activator of the oxidant. Low oxidation degree cannot effectively convert bound water into free water. Too high oxidation degree will significantly decompose sludge flocs, with more small particles and more water, resulting in difficulty in releasing bound water and deterioration of the filtration performance of sludge liquid / solid phase separation. Due to the different sludge pre-oxidation methods used in the prior art, the dehydration effect obtained is also different. At present, it is difficult to accurately determine the favorable pre-oxidation degree range according to the type and concentration of the oxidant.Therefore, it is necessary to find an indicator suitable for characterizing the oxidation process and explore the relationship between the oxidation process and sludge dewatering performance.
[0003] Chinese patent CN 108931563 B points out that conventional indicators for evaluating sludge dewatering performance, such as specific resistance, capillary water absorption time, sludge sedimentation coefficient, total content of extracellular polymers and protein content, tyrosine protein, tryptophan protein, humic acid, fulvic acid and soluble microbial metabolic byproducts, bound water content, iron content in dewatered cake and filtrate, sludge particle size, and zeta potential, cannot reflect the changes in the state of bound water and the transformation of hydrophilic organic matter; and the experimental error of bound water determination is large and the repeatability is poor; in addition, the extraction and determination of extracellular polymers have the disadvantages of requiring the addition of chemical agents, long time, cumbersome operation, and difficult quantitative analysis. Based on this, they proposed a method for quickly evaluating the dewatering performance of oxidatively conditioned sludge based on redox potential. However, this method has strict requirements on the initial pH value of the sludge, requiring the initial pH of the sludge to be 5.0-6.8. When the addition of oxidants causes the sludge pH to be acidic or alkaline, this method is not applicable. In addition, when there are some factors in the sludge that interfere with the determination of the redox potential, such as changes in the sludge temperature and dissolved oxygen content, the redox potential cannot be used to evaluate the dewatering performance of the oxidatively conditioned sludge.
[0004] The soluble organic matter in the sludge has a strong affinity for water, and its chemical composition will significantly affect the dewatering performance of the sludge. Chinese patent CN101980004B uses three-dimensional fluorescence spectroscopy and combines parallel factor analysis to divide DOM into different components for characterizing the dewatering performance of sludge. When log (component 1 score)>2.78, the sludge dewatering performance is considered to be poor, and when log (component 1 score)<2.67, the sludge dewatering performance is considered to be good. However, this invention patent only describes the relationship between the soluble organic matter components in the sludge and the sludge dewatering performance, and cannot be used to identify the effect of different pre-oxidation degrees on the dewatering performance of the sludge. In addition, the invention patent method requires that the soluble organic carbon of the tested sludge sample is less than 10 mg / L and the pH is 7. However, the soluble organic carbon content of most sludge samples will increase after the pre-oxidation process, and is much greater than 10 mg / L. The invention method is not suitable for evaluating the dewatering performance of sludge after pre-oxidation. Chinese patent CN109115712B invented a device and method for testing the electron transfer capacity of different molecular weight components of soluble organic matter, which can realize the simple and accurate determination of the electron transfer capacity of different molecular weight components in complex systems. Chinese patent CN102192942B discloses a method for quickly determining the electron transfer capacity of water-soluble organic matter, using the coulomb ampere method to determine the electron receiving and supply capacity of soluble organic matter, and the potential step method to determine the electron circulation capacity of soluble organic matter. Chinese patent CN109142243B discloses a method for determining the electron supply capacity of water-soluble organic matter using an ultraviolet spectrophotometer combined with spectroscopy. Chinese patent CN107255694B discloses a method for determining the electron supply capacity of water-soluble organic matter in water based on high performance liquid chromatography. However, the above patents all focus on the determination of the electron transfer capacity of soluble organic matter, and it is not clear whether they can be used to characterize the pre-oxidation and dehydration capacity of sludge. Chinese patent CN112851066B discloses a method for enhancing the electron transfer capacity of humic acid to promote anaerobic fermentation of sludge to produce acid. 2 The humic acid in the sludge hydrolyzate is catalytically reduced, so that the electron transfer capacity of the humic acid is enhanced, and the function of the humic acid as an electron intermediate or an anaerobic respiration electron acceptor in the sludge anaerobic fermentation system is strengthened, so as to improve the conversion rate of sludge organic matter. This patent improves the efficiency of sludge anaerobic digestion by strengthening the electron conversion capacity of sludge soluble organic matter. However, it is still unknown whether the electron conversion capacity of soluble organic matter in sludge can be used to evaluate the sludge dewatering performance during the pre-oxidation process. Summary of the invention
[0005] Based on this, the purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for evaluating the dewatering performance of pre-oxidation conditioned sludge based on the electron gain and loss capacity of soluble organic matter. The method is based on measuring the changes in the electron acceptance and supply capacity of soluble organic matter in the sludge, and quickly and effectively compares and evaluates the dewatering performance indicators of pre-oxidation chemical conditioning sludge. The patent of the present invention can measure the dewatering performance of pre-oxidation conditioned sludge, and is suitable for sludge with different initial pH and temperature, avoiding the problem of poor sludge dewatering performance caused by weak oxidation and strong oxidation caused by the inability to accurately and effectively evaluate the dewatering performance of sludge in pre-oxidation conditioning. Utilizing the present invention, the dosage of oxidizing agent in the pre-oxidation conditioning process can be reasonably controlled, and the sludge dewatering performance in the pre-oxidation process can be accurately and quickly evaluated.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for evaluating the dewatering performance of pre-oxidation conditioned sludge, comprising the following steps:
[0007] (1) Sample collection: The oxidant-treated sludge is centrifuged to obtain the sludge supernatant, and the soluble organic matter in the sludge is obtained by filtering the sludge through a membrane;
[0008] (2) Substitute into the formula; the dissolved organic matter electron accepting capacity S-EAC and dissolved organic matter electron donating capacity S-EDC caused by the oxidant and the sludge dewatering performance index satisfy the following relationship (S-EAC and S-EDC are expressed in absolute values):
[0009] |S-EAC| = -0.12 × CST - 0.01 × S-HS + 167.51 (1)
[0010] |S-EDC| = 0.01 × CST + 0.02 × S-HIX +136.57 × S-SUVA 254 - 10.05(2)
[0011] S-EAC refers to the electron accepting capacity of dissolved organic matter measured 20-60 minutes after adding the oxidant, and the unit is mmol e - / g TOC (total organic carbon); CST is the capillary absorption time, in seconds; S-HS is the content of humic acid in dissolved organic matter, in Raman units·L / g TOC (total organic carbon); S-EDC refers to the electron donating capacity of dissolved organic matter measured 20-60 minutes after the addition of oxidant, in mmol e - / g TOC (total organic carbon); S-HIX refers to the humification index of dissolved organic matter, in %; S-SUVA 254 Refers to the specific absorption coefficient of dissolved organic matter, the unit is L / g.cm2 ;
[0012] The present invention measures the electron acceptance and supply capacity of sludge soluble organic matter (soluble extracellular polymers) to compare and evaluate the influence of pre-oxidation conditioning on sludge dewatering performance. The soluble organic matter in sludge is composed of small molecular weight substances (free amino acids, organic acids, etc.) containing carboxyl groups, alcoholic hydroxyl groups and substituted amino groups and large molecular weight substances (enzymes, amino sugars, polyphenols and humus, etc.) containing phenolic hydroxyl groups, quinone groups and methoxy groups, and participates in many physical, chemical and biological processes. The quinone functional group contained in the structure of sludge soluble organic matter can complete the electron transfer process through the reversible transformation between quinone, semiquinone and hydroquinone. The addition of oxidant will inevitably cause changes in the electron acceptance and supply capacity of sludge soluble organic matter. Based on this, the ability of sludge soluble organic matter to accept and supply electrons can be used to quickly characterize the dewatering performance of pre-oxidized sludge.
[0013] Preferably, the electron-accepting ability of the soluble organic matter is caused by the carboxyl group on the aromatic substance; and the electron-donating ability of the soluble organic matter is caused by the aromatic group.
[0014] Preferably, the change in the electron acceptance and donation capacity of soluble organic matter in sludge caused by the oxidant specifically refers to the release of organic matter in the sludge-bound extracellular polymers into the dissolved extracellular polymers after the addition of the oxidant, thereby changing the change in the electron acceptance and donation capacity of the soluble organic matter.
[0015] Preferably, when the dissolved organic matter electron accepting capacity |S-EAC|>25.43 μmol e - / g TOC, and the electron donation capacity of dissolved organic matter |S-EDC|<1.59μmol e - / g TOC, the dewatering performance of pre-oxidation conditioned sludge is good.
[0016] Preferably, the sludge is anaerobic digestion sludge or residual activated sludge after acid or alkali treatment, the pH of the sludge before and after the oxidant conditioning is 2-14, and the sludge before the oxidant conditioning is the initial sludge (raw sludge).
[0017] The present invention is applicable to a wide range of sludge types and can be applicable to sludge of different pH values and temperatures.
[0018] Preferably, the total organic carbon content of the sludge before conditioning with the oxidant is greater than 200 mg / L.
[0019] Preferably, the oxidant is at least one of ozone, calcium hypochlorite, peracetic acid, potassium persulfate complex salt, chlorine dioxide, permanganate, and ferrate.
[0020] Preferably, the dosage of the oxidant is X, and X satisfies 0.1≤X<0.5mmol / g VS, and VS is the volatile solid matter content of the sludge before the oxidant conditioning.
[0021] Preferably, the oxidant conditioning time is 20-60 min, and the oxidant conditioning rotation speed is 100-500 rpm.
[0022] Preferably, the volume of the sludge is 0.05-50L.
[0023] Preferably, the rotation speed of the centrifugal treatment is 4000-7000 rpm.
[0024] Preferably, the pore diameter of the filter membrane is 0.2-0.45 μm.
[0025] Preferably, in step (2), the humification index S-HIX of the dissolved organic matter is tested as follows: it is calculated based on the ratio of the integral value of the fluorescence intensity at an excitation wavelength of 254 nanometers and the emission wavelengths of 435-480 nanometers and 300-345 nanometers, respectively.
[0026] Preferably, in step (2), the specific absorption coefficient S-SUVA of the soluble organic matter is 254 The test method is as follows: irradiate the sludge supernatant with ultraviolet light at a wavelength of 254 nanometers, and calculate the absorbance by dividing it by the TOC concentration (mg / L).
[0027] Preferably, in the step (2), the capillary absorption time CST is tested by calculating the time required for sludge water to penetrate a certain distance on the absorbent filter paper, and the content of humic acid substances in the soluble organic matter S-HS is tested by calculating the sum of the fluorescence intensities of humic acid substances and fulvic acid substances by the integration method using the three-dimensional excitation emission matrix (3D-EEM) fluorescence spectrum.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The sample requirement of the present invention is small, and the sample requirement can be as low as 50-100mL. 2. The sludge sample preparation process is simple and fast. The sample only requires a simple filtering operation, does not require any chemical agents, and the data processing is completed by a computer. 3. The present invention is simple and fast to operate. By measuring the values of the electron acceptance and supply capacity of the sludge soluble organic matter, the effect of oxidation conditioning can be judged in a short time, thereby evaluating its influence on the sludge dewatering performance. The present invention is applicable to a wide range of sludge types and can be applied to sludge of different pH and temperature. And the sensitivity is high. Compared with other indicators, the electron acceptance and supply capacity of soluble organic matter can more intuitively reflect the dosage of oxidizing agent, which can provide near real-time monitoring conditions for the operation of sludge dewatering equipment, facilitate the optimization and control of the addition of dehydrating agents, and save the cost of agents and monitoring. 4. Based on the present invention, the electron acceptance and supply capacity of sludge soluble organic matter can be used to judge the influence of oxidation conditioning on the sludge dewatering performance. The present invention is based on the characteristics of oxidative chemical conditioning sludge, and the changes in the electron acceptance and supply capacity of dissolved organic matter caused by the oxidant, to accurately judge the changes in sludge dewatering performance. The present invention can quickly and accurately evaluate and compare the effects of pre-oxidation on sludge dewatering performance without adding chemical reagents, and can be used to evaluate the dewatering performance of sludge produced in sewage treatment plants during pre-oxidation conditioning. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Flow chart for evaluating the dewatering performance of pre-oxidation conditioned sludge;
[0030] Figure 2 This is a correlation diagram of the electron accepting capacity and electron donating capacity of dissolved organic matter and the capillary water absorption time of sludge under different potassium persulfate compound salt dosages in sludge in implementation case 1;
[0031] Figure 3 This is a correlation diagram between the electron accepting capacity and electron donating capacity of dissolved organic matter and the sludge specific resistance at different potassium persulfate compound salt dosages in the sludge in implementation case 1;
[0032] Figure 4 This is a correlation diagram of the electron accepting capacity and electron donating capacity of dissolved organic matter and the capillary water absorption time of sludge under different potassium persulfate compound salt dosages in sludge in implementation case 2;
[0033] Figure 5 This is a correlation diagram between the electron accepting capacity and electron donating capacity of dissolved organic matter and the sludge specific resistance at different potassium persulfate compound salt dosages in the sludge in implementation case 2;
[0034] Figure 6This is a correlation diagram between the electron accepting capacity and electron donating capacity of dissolved organic matter and the zeta potential of sludge under different potassium persulfate compound salt dosages in sludge implementation case 2;
[0035] Figure 7 This is a correlation diagram between the electron accepting capacity and electron donating capacity of soluble organic matter and the median particle size of the sludge at different dosages of potassium persulfate compound salt in sludge implementation case 2. DETAILED DESCRIPTION
[0036] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.
[0037] The present invention provides a method for evaluating the dewatering performance of pre-oxidation conditioned sludge, comprising the following steps:
[0038] (1) Centrifuging the oxidant-treated sludge to obtain a sludge supernatant, and filtering the sludge with a membrane to obtain dissolved organic matter in the sludge;
[0039] (2) The electron accepting capacity (S-EAC) and electron donating capacity (S-EDC) of dissolved organic matter caused by oxidants and the sludge dewatering performance index satisfy the following relationship (S-EAC and S-EDC are expressed in absolute values):
[0040] |S-EAC| = -0.12 × CST - 0.01 × S-HS + 167.51 (1)
[0041] |S-EDC| = 0.01 × CST + 0.02 × S-HIX +136.57 × S-SUVA 254 - 10.05(2)
[0042] S-EAC refers to the electron accepting capacity of dissolved organic matter measured 20-60 minutes after adding the oxidant, and the unit is mmol e - / g TOC (total organic carbon); CST is the capillary absorption time, in seconds; S-HS is the content of humic acid in dissolved organic matter, in Raman units·L / g TOC (total organic carbon); S-EDC refers to the electron donating capacity of dissolved organic matter measured 20-60 minutes after the addition of oxidant, in mmol e - / g TOC (total organic carbon); S-HIX refers to the humification index of dissolved organic matter, in %; S-SUVA 254 Refers to the specific absorption coefficient of dissolved organic matter, the unit is L / g.cm 2 ;
[0043] Figure 1 Flowchart for evaluating the dewatering performance of pre-oxidation conditioned sludge.
[0044] In one embodiment, when the dissolved organic matter electron accepting capacity |S-EAC|>25.43 μmol e - / g TOC (total organic carbon), and the electron supply capacity of dissolved organic matter |S-EDC| <1.59μmol e - / g TOC (total organic carbon), the pre-oxidation sludge has good dewatering performance.
[0045] In one embodiment, there is a certain linear relationship between the electron acceptance and donation capacity of the dissolved organic matter in the sludge after the oxidant conditioning and the traditional index characterizing the dewatering performance of the sludge pre-oxidation process.
[0046] In one embodiment, the electron accepting and donating capacity of dissolved organic matter in the sludge after oxidant conditioning can be measured as a function of the dosage of different oxidants.
[0047] In one embodiment, the traditional indicators characterizing the dehydration performance of the sludge pre-oxidation process include capillary absorption time, specific resistance, median particle size of sludge floc particles, sludge Zeta potential, the ratio of dead cells to total sludge cells, the ratio of live cells to total sludge cells, the humification degree index of sludge soluble organic matter, the specific absorption coefficient of soluble organic matter, tryptophan proteins in sludge soluble organic matter, soluble microbial metabolic by-products in sludge soluble organic matter, humic acid substances in sludge soluble organic matter, β-folded structure in the secondary structure of sludge soluble organic matter protein, the ratio of α-helix to the sum of β-folded and random coils in the secondary structure of protein, etc.
[0048] In one embodiment, the capillary absorption time refers to the test method in The application of chitosan quaternaryammonium salt to replace polymeric aluminum ferric chloride for sewage sludge dewatering; the specific resistance refers to the test method in A novel approach for sludge deep-dewatering via flowing-out enhancement but not relying on cell lysis and bound water release; the median particle size of sludge floc particles refers to the method in Synergistic effect of organic matter-floc size-bound water and multifactorial quantitative model of optimal reagent demand in sewage sludge conditioning process prior to dewatering; the Zeta potential of sludge refers to the method in TA and CTAB treatment synergistically enhance activated sludge dewatering by lowering proteins and boosting zeta potential; the ratio of dead cells to total sludge cells and the ratio of live cells to total sludge cells refer to Toxicity of three crystalline TiO2 nanoparticles in activated sludge: bacterial cell death modes differentially weaken sludge The methods in dewaterability; the humification degree index of sludge dissolved organic matter, the specific absorption coefficient of soluble organic matter, the tryptophan proteins in sludge dissolved organic matter, the soluble microbial metabolic byproducts in sludge dissolved organic matter, and the humic acid substances in sludge dissolved organic matter all refer to the methods in Fluorescence excitation-emission matrix regional integration to quantify spectra for dissolved organic matter;The ratio of β-fold structure in the secondary structure of sludge dissolved organic matter protein and the sum of α-helix, β-fold and random coil in the secondary structure of protein refer to the method in Spectroscopic characterization of extracellular polymeric substances from amixed culture dominated by ammonia-oxidizing bacteria. ;
[0049] In one embodiment, first, the Pearson correlation is used to establish the correlation between the electron accepting and supplying capacity of dissolved organic matter and the sludge dewatering performance index and other characteristics of sludge organic matter, and the results are shown in Table 1. Secondly, the electron accepting and supplying capacity values of dissolved organic matter are normalized by total dissolved organic carbon (TOC), and the numerical value is expressed in mmol e - / g TOC. The relevant parameters were further selected and the multivariate linear regression equation was fitted using SAS software. The optimal prediction solution obtained by arranging and combining different variables (and the data in Table 1) was obtained to obtain Formula 1 and Formula 2.
[0050] The TOC test refers to the method in Variations in physical, chemical and biological properties in relation to sludge dewaterability under Fe(II)-Oxone conditioning.
[0051] The results are shown in Table 1 - Correlation between the electron acceptance and supply capacity of dissolved organic matter and sludge dewatering performance indicators and other characteristics of sludge organic matter. There is a certain linear relationship between the electron acceptance and supply capacity of dissolved organic matter and sludge dewatering performance indicators and other characteristics of sludge organic matter. The sludge types in Table 1 are sludge produced after anaerobic digestion of food waste.
[0052] Table 1
[0053]
[0054] Note: S-EAC represents the electron accepting capacity of dissolved organic matter; S-EDC represents the electron donating capacity of dissolved organic matter; CST represents the capillary absorption time; SRF represents the specific resistance; D 50It represents the median particle size of sludge flocs; Zeta represents the Zeta potential of sludge; Dead cells ratio represents the ratio of dead cells to total sludge cells; Live cells ratio represents the ratio of live cells to total sludge cells; HIX represents the humification degree index of sludge dissolved organic matter; SUVA represents the humification degree index of sludge dissolved organic matter; 254 = represents the specific absorption coefficient of dissolved organic matter; Region II represents tryptophan proteins in sludge dissolved organic matter; Region IV represents soluble microbial metabolic byproducts in sludge dissolved organic matter; Region V represents humic acid substances in sludge dissolved organic matter; β-sheet represents the β-folded structure of the secondary structure of proteins in sludge dissolved organic matter; β-sheet represents the ratio of α helix to the sum of β-folded and random coils in the secondary structure of proteins in sludge dissolved organic matter. NA indicates no significant correlation. * indicates significant correlation, and the statistical significance (p value) is less than 0.05; ** indicates significant correlation, and the statistical significance (p value) is less than 0.01.
[0055] In one embodiment, the method for measuring the electron gain and loss capacity of dissolved organic matter in the sludge after oxidant conditioning is to use a three-electrode electrochemical workstation to perform chronoamperometry, using three electrodes with an area of 17.5 cm 2 Graphite sheet electrode (working electrode), area 17.5cm 2 Platinum mesh electrode (counter electrode), Ag / AgCl electrode (reference electrode), potassium chloride phosphate mixed solution as electrolyte (pH = 7), phosphate as buffer; when measuring the electron accepting capacity, a negative potential of -0.6V is used for measurement, and when measuring the electron donating capacity, a positive potential of 0.5V to 0.6V is used for measurement. Before each measurement, N 2 The electrolytic cell was purged for 5 minutes to remove air. The electron accepting and donating capacities of dissolved organic matter were calculated according to the following formula (the calculated S-EAC and S-EDC were expressed in absolute values).
[0056]
[0057]
[0058] Among them, I red and I ox is the baseline-corrected reduction and oxidation current in amperes, m TOC is the total organic carbon content, in mg / L, and F is the Faraday constant (96485sA / mol e - ), t is the electron transfer time, in seconds.
[0059] This method refers to the method in Increased electron-accepting and decreased electron-donating capacities of soil humic substances in response to increasing temperature.
[0060] Implementation Case 1
[0061] This example is based on the electron gain and loss capacity of soluble organic matter in sludge, and the dewatering performance of sludge conditioned with different concentrations of the same oxidant is quickly compared and evaluated in the following steps:
[0062] (1) The sludge in this example was taken from Nanjing Jiushengmei Food Waste Disposal Co., Ltd. (the TOC concentration of the sludge supernatant was about 3396 mg / L, and the initial pH of the sludge was about 7.8). The sludge samples were collected and transported back in polypropylene barrels. The sludge was filtered through a 1 mm standard sieve to remove large sand and gravel, and stored in a 4°C freezer. Since the sludge is easily deteriorating, the experiments were completed within 3 days after the sludge was collected; the initial total solid content of the sludge was 28.1 g / L, and the volatile solid content was 13.3 g / L.
[0063] (2) Take 1000 mL of the original mud into a 2000 mL beaker, add 0-0.5 mmol / g VS potassium persulfate complex salt, and shake in a stirrer at 300 rpm for 30 min;
[0064] (3) Determine the electron acceptance and donation capacity of soluble organic matter in sludge after sludge conditioning with potassium persulfate complex salt at different concentrations;
[0065] (4) Determine the capillary absorption time and specific resistance of sludge after conditioning sludge with potassium persulfate complex salt at different concentrations;
[0066] In this implementation case, the electron accepting capacity and electron donating capacity of the raw mud dissolved organic matter are 4.6 (μmol e - / g TOC) and 3.1 (μmol e - / g TOC) (the ability to gain and lose electrons is expressed in absolute values).
[0067] After adding 0.5mmol / g VS potassium persulfate complex salt, the electron accepting capacity of the dissolved organic matter in the original mud increased from 4.6 (μmol e - / g TOC) increased to 33.4 (μmol e - / g TOC). The electron supply capacity of the dissolved organic matter in the raw mud ranges from 3.1 (μmol e - / g TOC) to 0.7 (μmol e - / g TOC) (the ability to gain and lose electrons is expressed in absolute values).
[0068] After adding potassium persulfate complex salt, the capillary water absorption time and specific resistance of the sludge showed the same downward trend, indicating that with the increase in the dosage of oxidizing agent, the sludge dehydration effect gradually improved.
[0069] Pearson correlation showed that the electron accepting capacity of dissolved organic matter was negatively correlated with the capillary water absorption time (R = -0.99, p < 0.01), and the electron donating capacity of dissolved organic matter was positively correlated with the capillary water absorption time (R = 0.97, p < 0.01) (the electron gain and loss capacity were both expressed in absolute values) ( Figure 2 );
[0070] The electron accepting capacity of dissolved organic matter was negatively correlated with the specific resistance (R=-0.88, p<0.05), and the electron donating capacity of dissolved organic matter was positively correlated with the specific resistance (R=0.82, p<0.05) (the electron gain and loss capacity were both measured in absolute values) ( Figure 3 ).
[0071] Combined with the obtained data, the dewatering performance of sludge meets the following conditions when the addition amount of potassium persulfate composite salt is ≥0.2mmol / g VS: Organic matter electron accepting capacity |S-EAC|>25.43μmol e - / g TOC, and the electron donation capacity of dissolved organic matter |S-EDC|<1.59μmol e - / g TOC condition. At this concentration, the sludge dewatering performance is significantly improved.
[0072] Implementation Case 2
[0073] This example is based on the electron gain and loss capacity of soluble organic matter in sludge, and the dewatering performance of sludge conditioned with different concentrations of the same oxidant is quickly compared and evaluated in the following steps:
[0074] (1) The residual activated sludge in this example was taken from Quxi BEIJING WATER CO., LTD., Jieyang, Shantou, Guangdong Province (TOC concentration of sludge supernatant was about 904 mg / L, initial pH of sludge was about 7.5, and pH after alkali treatment was about 10). The sludge samples were collected and transported back in polypropylene buckets. The sludge was filtered through a 1 mm standard sieve to remove large sand and gravel, and stored in a 4°C freezer. Since sludge is easily deteriorated, the experiments were completed within 3 days after sludge collection; the initial total solid content of the sludge was 27.4 g / L, and the volatile solid content was 12.3 g / L.
[0075] (2) In order to further increase the content of dissolved organic matter in the sludge and test whether this method is applicable to the condition where the initial sludge pH is alkaline, 500 mL of raw sludge was taken into a 1000 mL beaker, and the initial sludge pH was adjusted to 10 using 5 mol / L sodium hydroxide and 5 mol / L hydrochloric acid. Then, 0-0.5 mmol / g VS of potassium persulfate complex salt was added to the sludge after the pH 10 alkaline treatment. The mixture was shaken in a stirrer at 500 rpm for 20 min;
[0076] (3) Determine the capillary absorption time and specific resistance of sludge after conditioning the sludge with potassium persulfate complex salt at different concentrations;
[0077] (4) Determine the electron acceptance and donation capacity of soluble organic matter in sludge after the sludge is conditioned with potassium persulfate complex salt at different concentrations.
[0078] In this implementation case, the electron accepting capacity and electron donating capacity of the raw mud dissolved organic matter are 1.3 (μmol e - / g TOC) and 5.4 (μmol e - / g TOC) (the ability to gain and lose electrons is expressed in absolute values).
[0079] After adding 0.5mmol / g VS potassium persulfate complex salt, the electron accepting capacity of the dissolved organic matter in the original mud increased from 1.3 (μmol e - / g TOC) increased to 39.0 (μmol e - / g TOC). The electron supply capacity of the dissolved organic matter in the raw mud ranges from 5.4 (μmol e - / g TOC) was reduced to 2.9 (μmol e - / g TOC)(Electron gain and loss are both in absolute values)( Figure 4 ).
[0080] After adding potassium persulfate complex salt, the capillary water absorption time and specific resistance of the sludge showed the same downward trend, indicating that with the increase in the dosage of oxidizing agent, the sludge dehydration effect gradually improved.
[0081] Pearson correlation showed that the electron accepting capacity of dissolved organic matter was negatively correlated with the capillary water absorption time (R = -0.91, p < 0.05), and the electron donating capacity of dissolved organic matter was positively correlated with the capillary water absorption time (R = 0.87, p < 0.05) (the electron gain and loss capacity were both expressed in absolute values) ( Figure 4 );
[0082] The electron accepting capacity of dissolved organic matter was negatively correlated with the specific resistance (R=-0.95, p<0.01), and the electron donating capacity of dissolved organic matter was not correlated with the specific resistance (p>0.05) (the electron gain and loss capacity were both measured in absolute values) ( Figure 5 ).
[0083] The electron accepting capacity of dissolved organic matter was positively correlated with Zeta potential (R=0.92, p<0.01), while the electron donating capacity of dissolved organic matter was not correlated with Zeta potential (p>0.05) (the electron gain and loss capacity were both expressed in absolute values) Figure 6 ).
[0084] The electron accepting capacity of dissolved organic matter was negatively correlated with the median particle size (R=–0.92, p<0.01), and the electron donating capacity of dissolved organic matter was not correlated with the median particle size (p>0.05) (the electron gain and loss capacity were both measured in absolute values) ( Figure 7 ).
[0085] Combined with the obtained data, the dewatering performance of the sludge meets the following conditions when the addition amount of potassium persulfate composite salt is 0.3mmol / g VS: Organic matter electron accepting capacity |S-EAC|>25.43μmol e - / g TOC, and the electron donation capacity of dissolved organic matter |S-EDC|<1.59μmol e - / g TOC condition. At this concentration, the sludge dewatering performance is significantly improved. When the dosage of potassium persulfate composite salt is greater than this concentration, the capillary water absorption time changes from decreasing with the increase of oxidant dosage to increasing with the increase of oxidant dosage.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for evaluating the dewatering performance of pre-oxidation conditioned sludge, characterized in that: The following steps are involved: (1) Centrifuging the oxidant-treated sludge to obtain a sludge supernatant, and filtering the sludge with a membrane to obtain soluble organic matter in the sludge; (2) The electron accepting capacity (S-EAC) and electron donating capacity (S-EDC) of dissolved organic matter caused by oxidants and the sludge dewatering performance index satisfy the following relationship, where S-EAC and S-EDC are expressed in absolute values: |S-EAC| = -0.12 × CST - 0.01 × S-HS + 167.51 (1) |S-EDC| = 0.01 × CST + 0.02 × S-HIX +136.57 × S-SUVA 254 - 10.05 (2) S-EAC refers to the electron accepting capacity of dissolved organic matter measured 20-60 minutes after adding the oxidant, and the unit is mmol e - / g TOC; CST is the capillary absorption time, in seconds; S-HS is the content of humic acid in dissolved organic matter, in Raman units·L / g TOC; S-EDC refers to the electron donating capacity of dissolved organic matter measured 20-60 minutes after the addition of oxidant, in mmol e - / g TOC; S-HIX refers to the humification index of dissolved organic matter, in %; S-SUVA 254 Refers to the specific absorption coefficient of dissolved organic matter, the unit is L / g.cm 2 .
2. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: When the electron accepting capacity of dissolved organic matter |S-EAC|>25.43μmol e - / g TOC, and the electron donation capacity of dissolved organic matter |S-EDC|<1.59μmol e - / g TOC, the dewatering performance of pre-oxidation conditioned sludge is good.
3. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: In the step (1), the pH of the sludge before and after the oxidant conditioning is 2-14.
4. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: In the step (1), the total organic carbon content of the sludge before the oxidant conditioning is greater than 200 mg / L.
5. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: The oxidant is at least one of ozone, calcium hypochlorite, peracetic acid, potassium persulfate complex salt, chlorine dioxide, permanganate, and ferrate.
6. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: The dosage of the oxidant is X, and X satisfies 0≤X<0.5mmol / g VS, and VS is the volatile solid matter content of the sludge before the oxidant conditioning.
7. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: The conditioning time of the oxidant is 20-60 minutes, and the rotation speed of the oxidant conditioning is 100-500 revolutions per minute.
8. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: The volume of the sludge before the oxidant conditioning is 0.05-50L.
9. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: The rotation speed of the centrifugal treatment is 4000-7000 rpm.
10. The method for evaluating the dewatering performance of pre-oxidation conditioned sludge according to claim 1, characterized in that: The pore diameter of the filter membrane is 0.2-0.45 μm.
Citation Information
Patent Citations
Method for rapidly representing sludge dewatering performance
CN101980004B
Method for rapidly determining electron transfer capacity of DOM (dissolved organic matter)
CN102192942B
Sludge-dewatering compound conditioning agent and application method thereof
CN102381828A
An iron salt sludge dewatering agent and a sludge dewatering method
CN103663920B
A method for determining the electron-donating ability of water-soluble organic compounds in water based on high-performance liquid chromatography.
CN107255694B
Cited By
Biogas residue humification degree rapid characterization method based on spectrum and chemical indications
CN120801215A